In vivo Pharmacokinetic Pharmacodynamic Relationship and in vitro Equivalence of Two Oral Furosemide Tablet Formulations - Cuadrado, Antonio; Gascón, Alicia Rodŕıguez; Hernaández, Rosa Maŕıa; Castill, Ana Maŕıa; Maza, Ane de la; Y´nez, Carlos; Lópezde, Alicia Oćriz; Angeles, M. Solinís; Pedraz, José Luis (Arzneimittelforschung, 2003)
A randomized, cross-over, open study of bioequivalence between two different furosemide (CAS 54-31-9) formulations was performed; simultaneously, diuretic effects (urine output, sodium, potassium and chloride excretion) were also compared. Both products meet the British Pharmacopoeia specification and the results of a previous in vitro comparative study ensure equivalence of the two dissolution curves. Twenty-four healthy volunteers (male/female) participated in the bioequivalence study. Each treatment was given as a single 40-mg tablet following an overnight fast. Furosemide concentrations in plasma (measured by HPLC) and electrolyte amounts in urine were determined up to 12 h after treatment. The pharmacokinetic parameters AUC0–∞, Cmax and Cmax/AUC0–∞ were tested for bio-equivalence after ln-transformation of data and ratios of tmax were evaluated nonparametrically. The parametric analysis revealed the following test/reference ratios and their 90 % confidence intervals (90 % CI): 1.06 (0.94−1.19) for AUC0–∞, 1.12 (0.96−1.31) for Cmax, and 1.06 (0.97−1.16) for Cmax/AUC0–∞. The 90 % CI for tmax was 0.55−1.00. Bioequivalence between both formulations was concluded for all parameters except for tmax. No significant diuretic differences between both formulations (test and reference) were observed after drug administration in relation to the baseline period. Systolic and diastolic blood pressure and heart rate showed a similar time-course after the drug administration and there were no differences between both formulations. Both products were well tolerated. It can be concluded that both formulations are equivalent in vitro and in vivo.
Keywords: CAS 54-31-9; Furosemide, bioavailability, bioequivalence, in vitro and in vivo studies; pharmacodynamics, pharmacokinetics; Furosemide CINFA®